Student Responses on The Application of Hypnoteaching Method in Learning Hindu Religious Education - Ida Bagus Alit Arta Wiguna (Jurnal Pendidikan dan Pengajaran, 2020)
This research aims to identify and analyse students’ response on the application of the Hypnoteaching in learning Hindu religious education in class X of SMAN 7 Denpasar. This research follows a qualitative approach with observation as the main data collection technique. The sample of the study is X MIPA 6 class with 34 students from a total of 389. The application of hypnoteaching methods is fun for students compared to conventional methods which tend to be uninteresting. When using Hypnoteaching method, students were very excited during learning activities. By using hypnoteaching methods in learning Hindu religious education students becomes very enthusiastic in listening to the teacher's explanation of Hindu religious learning materials. To improve learning activities students prepare themselves for the topic discussion. Students’ response to the application of Hypnoteaching method is positive. They think that the method is effective as it can increase students’ enthusiasm to learn.